Meteorological Drought Analysis in Tangsi Sub-Watershed, Magelang Regency - Atikah, A; Pradita, Rey Pingkan; Ramadhania, Rizka Novi; Naim, Asshaffa; Paramesthi, Febriyanti; Anjani, Azzahra Gita Putri; Ramadhanissa, Diandra Salma; Fathurrahman, Yusuf; Khansa, Lulu Nabila; Oktaviani, Malinda Budi; Abidin, Pramuditya Vanesya Putri Febrian; Mahdi, Naufal Asyraf; Suarma, Utia (Universitas Muhammadiyah Surakarta, 2024)
Natural disasters such as droughts occur gradually and last until the start of the rainy season. Meteorological drought happens when a region experiences periods of below-average rainfall, resulting in lower water availability in the soil compared to its needs. The Tangsi Sub-Watershed traverses the districts of Kajoran, Salaman, Kaliangkrik, Borobudur, and Tempuran. It is part of the Progo Watershed, which is under the administrative boundary of Magelang Regency. The variation in climate and the landforms of the Tangsi Sub-Watershed, which are dominated by materials that are less permeable to water, make this area prone to drought. This research analyzes meteorological drought in the Tangsi Sub-Watershed, Magelang Regency by using the Standardized Precipitation Index (SPI) and Drought Hazard Index (DHI). The analysis from quarterly SPI from 1994 to 2023 indicates that the Tangsi Sub-Watershed experienced a medium drought hazard level with a score of 14. The Tangsi Sub-Watershed experienced extreme drought events at 2.22%, high drought at 3.89%, and moderate drought at 6.94%. Long-term drought risk analysis can be used by communities and governments to plan and implement mitigation measures ahead of time by revealing patterns and intensities of recurrent droughts.